Political and religious aspects of community according to Kant - Margit Ruffing (Ethic@: an International Journal for Moral Philosophy)
Based on the concept of community, Kant's conception of religion may be connected, on my view, to the question of which mental attitude is suitable for the collective life of human society. It is possible to imagine a successful community, even if such a community does not exist in the empirical world, and to be oriented toward this ideal without ever being able to realize it. According to Kant, human moral self-understanding is developed by human reason, and this explains the structural similarity between the secular republic and the Kingdom of God under the specific conditions of the enlightened consciousness of a person who thinks for herself. Thus the anthropological "fact": the self-understanding of the human being characterised by his faculty of reason.